Legal Concept of Corporate Income Tax Rates In The Work Agreement For The 3rd Generation Coal Mining Company To Create Legal Certainty - Jukipli, Jukipli; Ismail, Ismail; Hartana, Hartana (Ilmu Hukum Prima (IHP), 2026)
This study examines the normative disharmony between the provisions of Corporate Income Tax (PPh) in the Generation III Coal Mining Work Agreement (PKP2B) and the generally applicable PPh Law. Article 14 number 3 letter i of the Generation III PKP2B sets a maximum progressive rate of 30% for Taxable Income above Rp50,000,000, but also contains a clause that allows for a lower rate through Government Regulations and adjustments to the PKP layer through a Decree of the Minister of Finance. Meanwhile, the PPh Law has reduced the Corporate Income Tax rate from 25% to 22% through the Law on Harmonization of Tax Regulations (UU HPP). The difference in interpretation gives rise to two conflicting principles: "nailed down"—as interpreted by the Directorate General of Taxes, which freezes rates at the time of contract signing—and "prevailing"—as contractors claim to follow generally applicable rates over time. This research uses a normative juridical method with a statutory, conceptual, and case-based approach. The research findings indicate that the absence of specific implementing regulations does not create legal uncertainty, as higher-level laws—the Income Tax Law and the HPP Law—are hierarchically superior. Contract clauses that allow for lower rates and adjustments to the PKP layer implicitly support the application of the prevailing principle. Therefore, the corporate income tax rate for Generation III PKP2B contractors should follow the generally applicable tariff provisions over time, in order to achieve legal certainty, hierarchical alignment of norms, and fiscal justice.   Penelitian ini bertujuan untuk menganalisis ketidakharmonisan norma antara Perjanjian Karya Pengusahaan Pertambangan Batubara Generasi III dan Undang-Undang Pajak Penghasilan serta merumuskan konsep hukum pengenaan tarif Pajak Penghasilan Badan yang ideal guna mewujudkan kepastian hukum dan keadilan fiskal. Metode Penelitian yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan kasus, melalui analisis terhadap peraturan, kontrak, dan putusan pengadilan.   Hasil penelitian menunjukan meskipun hingga kini belum diterbitkan Peraturan Pemerintah atau Keputusan Menteri Keuangan yang secara khusus mengatur tarif Pajak Penghasilan dan lapisan Penghasilan Kena Pajak bagi Perusahaan Kontraktor Perjanjian Karya Pengusahaan Pertambangan Batubara Generasi III, hal tersebut tidak menimbulkan permasalahan hukum karena ketentuan tarif telah diatur dalam Undang-Undang Pajak Penghasilan dan Undang-Undang Harmonisasi Peraturan Perpajakan yang secara hierarki memiliki kedudukan lebih tinggi berdasarkan Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-undangan. Dengan demikian, tarif Pajak Penghasilan Badan dalam Perjanjian Karya Pengusahaan Pertambangan Batubara Generasi III seharusnya mengikuti ketentuan dalam Undang-Undang Pajak Penghasilan yang berlaku umum dan dari waktu ke waktu, karena frasa “atau tarif yang lebih kecil yang ditetapkan dengan Peraturan Pemerintah” dan frasa “Apabila lapisan penghasilan kena pajak diubah dengan Keputusan Menteri Keuangan, maka tarif tersebut diterapkan terhadap lapisan kena pajak yang telah diubah tersebut” dalam perjanjian memberikan dasar hukum bagi penerapan prinsip prevailing, yaitu penyesuaian terhadap tarif umum yang lebih rendah dikemudian hari tanpa melanggar ketentuan kontraktual.